ANALISIS KOMPARATIF KINERJA KEUANGAN PERUSAHAAN ASURANSI ALLIANZ LIFE INDONESIA DAN AXA MANDIRI (Pada Tahun 2011 – 2015) - Priska Oktafiani Putri; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2017)
Life Insurance Company is a company engaged in the service business. Currently the competition of insurance companies in Indonesia are getting tighter. One thing that can do to win the competition is improve the company’s financial performance.This study intends to analyze the company’s financial performance at PT.Allianz Life Indonesia and PT.AXA Mandiri period 2011 – 2015 based on regulation of SOEs Number : PER-10/MBU/2014 about the rating of State – Owned Enterprises in its financial aspects. Then from the results of this study compared to that obtained by the company,s financial performance which are the most good. The method used in this research is analytical descriptive research type. In analyzing the financial performance of life insurance companies are using financial statement analysis techniques in the form of the ratio analysis based on state regulation Number : PER-10/MBU/2014 which are Liquidity from Current Ratio, Solvability from Risk Based Capital (RBC), Profitability from Return on Asset (ROA) and Return on Equity (ROE).The result of this study indicate that financial performance of PT. Allianz Life Indonesia isn’t better than PT. AXA Mandiri, especially from the level of ROA and ROE. But, based on regulation of SOEs Number : PER-10/MBU/2014 starting from 2011 – 2012 the financial performance of PT. Allianz Life Indonesia include into category KURANG SEHAT BBB. Starting from 2013 – 2015 PT. Allianz Life Indonesia include into category SEHAT A. While PT. AXA Mandiri starting from 2011 – 2015 always include into category SEHAT A. The conclusion based on percentage ratio and state regulation Number : PER-10/MBU/2014 showed that AXA Mandiri is better than Allianz Life Indonesia, the best financial performance also obtained by AXA MAndiri with score 80% and include into category SEHAT A.For PT. Allianz Life Indonesia shoudly improve the current assets and reduce the fixed assets or sell the unproductive fixed assets. In the other side, Allianz Life Indonesia can increase the revenue and reduce the burden.